This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since
n → ∞ lim ln ( n n 1 ⋅ n 2 ⋯ n n ) = n → ∞ lim n 1 ( k = 1 ∑ n ln ( n k ) ) = ∫ 0 1 ln ( x ) d x = − 1
We have n n ! 1 ∼ n e as n → ∞ . Thus, it suffices to prove that lo g a ( k = 1 ∑ a n ( 1 + k ) a − n ) ∼ n as n → ∞ .
Now,
a n ⋅ 2 1 / a n ≤ k = 1 ∑ a n ( 1 + k ) a − n ≤ a n ( 1 + a n ) 1 / a n
and therefore using the fact that lo g a is increasing,
n + a n lo g a ( 2 ) ≤ lo g a ( k = 1 ∑ a n ( 1 + k ) a − n ) ≤ n + a n n + a n 1 lo g a ( 1 + a n 1 ) .
The squeeze principle now shows that
n → ∞ lim n 1 lo g a ⎝ ⎛ k = 1 ∑ a n ( 1 + k ) a − n ⎠ ⎞ = 1
And thus we obtain L = e ≈ 2 . 7 1 8